Polymer/Carbon Nanotube Nanocomposites: A Novel Material - KUMAR SWAIN*, SARAT; JENA, ITISHREE (Asian Journal of Chemistry, 2009)
Polymer/carbon nanotubes (CNTs) nanocomposites have been fabri-cated for its good processability characteristics of the polymer andexcellent functional properties of the CNTs. It is a problem how to enhance dispersion of CNTs in the polymer matrix. Present review deals with recent trends and advances that have been made. The dispersion of CNTs in a polymer matrix can be achieved including optimum blending, in situ polymerization and chemical functionalization. The alignment of CNTs in the matrix can possible to enhance by in situ techniques, force and magnetic fields, electro spinning and liquid crystalline phase-induced methods. Further, it is discussed on mechanical, thermal, electrical, electrochemical, optical and super-hydrophobic properties and applications of polymer/CNT composites. The enhancement in dispersion and alignment of CNTs in the polymer matrix will promote and extend the applications for developments of polymer/CNT nanocomposites. An improvement of the physical properties of polymer nanocomposites, based on CNTs, is passionated to a good dispersion and strong interactions between the matrix and the filler.